Cancer immunotherapy insights: key takeaways from the ADSCC bone marrow and cellular therapy congress 2024 - Suárez Formigo, Gisela Maria; Mazorra, Zaima; Olexen, Cinthia; Menéndez, Tamara; Abdel Hadi, Loubna; Handgretinger, Rupert; Bencomo Hernandez, Antonio Alfonso; El Najjar, Inas; Coukos, George; Sabzevari, Helen; Bollard, Catherine; Couriel, Daniel; et al. (Frontiers in Immunology, 2026)
The rising global cancer burden underscores the urgent need for innovative and effective therapies. Molecular and cellular immunology advances have revolutionized cancer immunotherapy, transforming laboratory discoveries into clinical breakthroughs. The Second Bone Marrow Transplant and Cellular Therapy Congress, held in Abu Dhabi, United Arab Emirates (UAE), on October 26th - 27th, 2024, and sponsored by the Abu Dhabi Stem Cells Center (ADSCC), convened global experts to discuss cutting-edge developments in adoptive cell transfer (ACT); chimeric antigen receptor T-cell (CAR-T) therapy, tumor-infiltrating lymphocyte (TIL) engineering and T-cell receptor (TCR) innovations. Discussions covered key challenges such as tumor microenvironment (TME) resistance, antigen escape, manufacturing complexity, cost-effectiveness, and accessibility. Experts emphasized the crucial role of biomarker identification in optimizing patient selection and improving treatment efficacy. Additionally, emerging strategies were highlighted to enhance the durability and specificity of cellular therapies, including next-generation CAR-T designs, combination approaches, and novel gene-editing technologies. With over 2,300 participants from academia, research, and healthcare, the event fostered international collaborations and knowledge exchange. The ADSCC continues to play a pivotal role in integrating advanced cellular therapies into healthcare systems, contributing to the expansion of precision oncology in the UAE and beyond. This review analyzes the latest advances in immunotherapy, highlighting their clinical impact, challenges, and future directions in the evolving landscape of cancer treatment, as debated during the congress.